Emotional fronto‐cingulate cortex activation and brain derived neurotrophic factor polymorphism in premenstrual dysphoric disorder. Issue 9 (25th February 2014) - Comasco, Erika; Hahn, Andreas; Ganger, Sebastian; Gingnell, Malin; Bannbers, Elin; Oreland, Lars; Wikström, Johan; Epperson, C. Neill; Lanzenberger, Rupert; Sundström‐Poromaa, Inger
Abstract Premenstrual dysphoric disorder (PMDD) is the prototypical sex‐specific disorder in which symptom onset and offset require a particular hormonal milieu and for which there is moderate heritability. The present study investigated brain emotion processing in PMDD and healthy controls, as well as functional polymorphisms in two candidate genes for PMDD, the serotonin transporter (5‐HTT) and brain derived neurotrophic factor (BDNF). The 5‐HTT linked polymorphic region (5‐HTTLPR) and BDNF Val66Met polymorphisms were genotyped in 31 patients with PMDD and 31 healthy controls. A subset of 16 patients and 15 controls participated in two functional magnetic resonance imaging‐sessions performing an emotion processing task; once in the mid‐follicular, and once in the late luteal phase which corresponds with maximum severity of mood symptoms. Genotypes were not directly associated with PMDD. A main effect of group was found in the whole brain analysis, with patients having lower activation of the pre‐genual anterior cingulate and ventro‐medial prefrontal cortex, independent of menstrual cycle phase. Post‐hoc functional ROI analyses in the fronto‐cingulate cluster showed no effect of 5‐HTTLPR genotype but a genotype‐by‐group‐by‐phase interaction effect of BDNF Val66Met. Women with PMDD who were carriers of the Met‐allele had lower fronto‐cingulate cortex activation in the luteal phase compared to Met‐allele carrying controls. The results provide suggestive evidence of impaired emotion‐induced fronto‐cingulate cortex activation in PMDD patients. Although limited by a small sample, the potential influence of BDNF Val66Met in PMDD is in line with preclinical findings. Hum Brain Mapp 35:4450–4458, 2014. © 2014 The Authors. Human Brain Mapping Published by Wiley Periodicals, Inc.